2017
DOI: 10.20307/nps.2017.23.3.217
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Constituents from the Rhizomes ofOsmunda japonicaThunb and Their Anti-oxidant Activity

Abstract: − Eleven compounds (1-11) were isolated from the rhizomes of Osmunda japonica, and their structures were elucidated based on 1 H, 13C-NMR and LC-IT-TOF MS data. Of these compounds, all compounds (1 -11) have been previously reported, although five (6 -9, 11) have not previously been isolated from this plant. The antioxidant activities of isolated compounds (1 -11) were measured by DPPH and ABTS assays, and compound 10 showed the high antioxidant activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…The structures of 29 known compounds were confirmed as bersimoside I ( 1 ), 22 abrisaponin L ( 2 ), 23 kuzusapogenol A methyl ester ( 3 ), 24 subproside I methyl ester ( 4 ), 25 subproside IV methyl ester ( 5 ), 26 subproside I ( 6 ), 25 sophoraflavone A ( 8 ), 27 vitexin-2″- O -rhamnoside ( 9 ), 17 bayin ( 10 ), 6 lyoniresinol ( 11 ), 28 (+) - isolariciresinol ( 12 ), 29 maltol- O -β- d -glucopyranoside ( 13 ), 30 licoagroside B ( 14 ), 31 5″-methyl-licoagroside B ( 15 ), 31 oxymatrine ( 16 ), 32 dimethyl (2 S ,3 R )-(+)-2-(4-hydroxybenzyl)tartrate ( 18 ), 20 2-(4-hydroxybenzyl) tartrate ( 19 ), 33 4-methyl eucomate ( 20 ), 34 dimethyl eucomate ( 21 ), 34 5-methyluracil ( 22 ), 35 uracil ( 23 ), 35 1,4-dihydroxy-2-methoxybenzene 4- O -β- d -glucopyranoside ( 24 ), 36 4-hydroxybenzoic acid 4-O-β- d -glucopyranoside ( 25 ), 37 gallic acid ( 26 ), 38 4-hydroxybenzoic acid ( 27 ), 39 trimethyl citrate ( 28 ), 40 3-hydroxy-3-methyl- 1,5-dimethyl ester ( 29 ), 41 ethyl-β- d -glucopyranoside ( 30 ), 42 and 1- O -methyl-inositol ( 31 ) 43 ( Figure S1 ) by comparing the measured spectroscopic data with the published values.…”
Section: Resultsmentioning
confidence: 99%
“…The structures of 29 known compounds were confirmed as bersimoside I ( 1 ), 22 abrisaponin L ( 2 ), 23 kuzusapogenol A methyl ester ( 3 ), 24 subproside I methyl ester ( 4 ), 25 subproside IV methyl ester ( 5 ), 26 subproside I ( 6 ), 25 sophoraflavone A ( 8 ), 27 vitexin-2″- O -rhamnoside ( 9 ), 17 bayin ( 10 ), 6 lyoniresinol ( 11 ), 28 (+) - isolariciresinol ( 12 ), 29 maltol- O -β- d -glucopyranoside ( 13 ), 30 licoagroside B ( 14 ), 31 5″-methyl-licoagroside B ( 15 ), 31 oxymatrine ( 16 ), 32 dimethyl (2 S ,3 R )-(+)-2-(4-hydroxybenzyl)tartrate ( 18 ), 20 2-(4-hydroxybenzyl) tartrate ( 19 ), 33 4-methyl eucomate ( 20 ), 34 dimethyl eucomate ( 21 ), 34 5-methyluracil ( 22 ), 35 uracil ( 23 ), 35 1,4-dihydroxy-2-methoxybenzene 4- O -β- d -glucopyranoside ( 24 ), 36 4-hydroxybenzoic acid 4-O-β- d -glucopyranoside ( 25 ), 37 gallic acid ( 26 ), 38 4-hydroxybenzoic acid ( 27 ), 39 trimethyl citrate ( 28 ), 40 3-hydroxy-3-methyl- 1,5-dimethyl ester ( 29 ), 41 ethyl-β- d -glucopyranoside ( 30 ), 42 and 1- O -methyl-inositol ( 31 ) 43 ( Figure S1 ) by comparing the measured spectroscopic data with the published values.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that B. striata contains stilbenes (bibenzyls and phenanthrenes) and polysaccharides [9,10]. There has been evidence that stilbenes from B. striata (BSS) possess anti-inflammatory, antitumor, and antibacterial properties [11,12], indicating that BSS has medical benefits to be promising healthcare products.…”
Section: Introductionmentioning
confidence: 99%